Equinodermos del Área de Conservación Guanacaste, Pacífico Norte de Costa Rica - Chacón-Monge, José-Leonardo (Universidad de Costa Rica, 2021)
ntroduction: The study of the marine diversity of the North Pacific of Costa Rica began with isolated foreign expeditions in the 1930s and was systematically developed in the mid-1990s by the Center for Research in Marine Sciences and Limnology, Universidad de Costa Rica, as consequence there are now a total of 1 479 reported species in this region. Objective: Present an update to the echinoderm richness of the Guanacaste Conservation Area. Methods: We sampled 25 localities exhaustively and estimated similarity between sites based on the family richness and environmental heterogeneity. Results: We found 61 taxa, which represent 26 % of the echinoderm reported species for the country’s Pacific coast. Of these, 43 species are new records for the Guanacaste Conservation Area, and seven for Costa Rica and Central American Pacific coasts. We found three morpho-species that do not match to available descriptions of the Eastern Tropical Pacific echinoderm species. We also found the holothuroid Epitomapta tabogae, and the ophiuroid Ophioplocus hancocki, previously thought endemic to Panama and the Galapagos Islands, respectively. The proximity of the sampled sites and the redundancy of certain families may explain why we did not find important differences among localities. Conclusions: The echinoderm richness of this conservation area is at least 20 % higher than previously reported, reaching similar levels to those in other high diversity sites of the Eastern Tropical Pacific.